Relationships between the neuro-endocrine parameters and virtual chakras energy and asymmetry - Valeriy Babelyuk; Ruslan Tserkovniuk; Galyna Dubkova; Yuriy Kruhliy; Tetyana Korolyshyn; Nazariy Babelyuk; Walery Zukow; Sofiya Ruzhylo; Oksana Fihura; Anatoliy Gozhenko; Igor Popovych (Kazimierz Wielki University, 2022)
Background. Earlier, we found a close correlation between EEG and gas-discharge image (GDI) parameters. The aim of this study is to analyze the relationship of EEG parameters with the energy and asymmetry of virtual chakras, reconstructed on the basis of GDI parameters. Material and Methods. We observed twice 31 women and 29 men aged 26-76 years with dysfunction of neuroendocrine-immune complex. In the morning in basal conditions at first registered GDI by the method of GDV by the device "GDV Chamber" ("Biotechprogress", SPb, RF). Than we registered EEG. Results processed by method of canonical analysis, using the software package "Statistica 64". Results. The coefficients of canonical correlation between the EEG parameters and virtual Chakras Energy are in the interval 0,415÷0,564 and 0,358÷0,528 when registering without a filter and with a filter, respectively. Additional inclusion of HRV and endocrine parameters increases the strength of the canonical correlation to 0,768 and 0,772, respectively. The coefficients of canonical correlation between the EEG parameters and individual virtual Chakras Asymmetry are in the interval 0,284÷0,634 and 0,152÷0,458 when registering without a filter and with a filter, respectively. Integral coefficient of the canonical correlation is 0,820. Conclusion. The above data, taken together with the previous ones, state that between parameters of neuroendocrine-immune complex and GDV exist strong canonical correlation suggesting suitability of the latter method.